Evaluation of Counterterrorism Policy in Poso District, Central Sulawesi Province - Dirham Herlib; Nuraisyah; Nawawi Natsir (Universitas Islam Balitar, 2026)
This research aims to evaluate the counter-terrorism policy in Poso Regency, Central Sulawesi Province. Poso Regency is one of the areas that has experienced horizontal conflict and became a base for terrorism movements in Indonesia. This research uses a descriptive qualitative approach with policy evaluation theory from Dunn and Ripley which includes seven evaluation aspects: measuring program effects, measuring compliance, providing explanation, obtaining information, providing feedback, conducting auditing, and providing recommendations. Research informants consist of the people of Poso Regency, task implementing officers, local government, and village officials. Data collection techniques were conducted through observation, in-depth interviews, documentation studies, and literature review. The results show that the implementation of counter-terrorism policies in Poso Regency refers to Law Number 5 of 2018 concerning Eradication of Criminal Acts of Terrorism with soft approach and hard approach. This policy evaluation is important to provide recommendations for improvement in terrorism prevention and handling efforts in the future and to ensure the security and survival of the community in Poso Regency.